KEWENANGAN MAHKAMAH KONSTITUSI TERHADAP PUTUSAN PERKARA NOMOR 90/PUU-XXI/2023 - Ichsan, Moch.; Irawan, Anang Dony (Universitas Gorontalo, 2024)
The decision of the Constitutional Court in case Number 90/PUU-XXI/2023 in the general election trial Number 7 of 2017, the opinions of legal experts and the public are contradictory. There are political parties who say the decision is right, and there are also those who say the Constitutional Court's decision is wrong. Furthermore, the problem formulated in this study is based on this background, namely the competence of the Constitutional Court and the legal consequences of its decisions. The research method is a normative and applicable legal approach. This research uses library research, namely. Qualitative studies are carried out by collecting library materials, reading and taking notes, and carrying out analysis on library materials that have been selected for use. Based on the results of this research, the Constitutional Court has the competence to make decisions on matters relating to the age limit for candidates for President and Vice President, where the court's decision is definite and binding.